Elevated CO2 Suppresses the Vanadium Stress in Wheat Plants under the Future Climate CO2 - Emad A. Alsherif; Hamada AbdElgawad (Plants, 2023)
Increases in atmospheric CO2 is known to promote plant growth under heavy metals stress conditions. However, vanadium (V) stress mitigating the impact of eCO2 as well as the physiological and biochemical bases of this stress mitigation have not been well studied. To this end, this study investigated the growth, photosynthetic parameters, oxidative damages antioxidants, and antioxidants enzymes in wheat plants grown under ambient (420 PPM) and high eCO2 (720 ppm) levels. Exposing wheat plants to higher V increased its accumulation in plants which consequentially inhibited plant growth and induced oxidative damage. An increase in antioxidant and detoxification defense systems was observed but it was not enough to reduce V stress toxicity. On the other hand, wheat growth was improved as a result of reduced V uptake and toxicity on photosynthesis under eCO2. To reduce V uptake, wheat accumulated citric acid, and oxalic acid in soil preferentially under both treatments but to more extend under V and eCO2. Additionally, improved photosynthesis induced high carbon availability that was directed to produce chelating proteins (metallothioneins, phytochelatin) and antioxidants (phenolics, flavonoids, total antioxidant capacity). This study advances our knowledge of the processes behind the variations in the physiological and biochemical responses of the wheat crop under V and eCO2 conditions.